Structure and Function Relationship of Activated Retinal Glia in Primary Open-Angle Glaucoma Patients - Christoph Nützi; Andreas Schötzau; Matthias C. Grieshaber (Journal of Ophthalmology)
Purpose. To evaluate clinically activated retinal astrocytes and Müller cells (ARAM) regarding retinal sensitivity and retinal nerve fiber layer (RNFL) thickness in primary open-angle glaucoma (POAG). Methods. Central visual field (VF; i.e., retinal sensitivity) was measured with a custom-made macular pattern by microperimetry and correlated with the presence (ARAM+) or absence (ARAM−) of ARAM on red-free fundus photography and with the corresponding RNFL by optical coherence tomography (OCT). Results. In the eyes of POAG patients, ARAM+ had overall a significantly lower retinal sensitivity (ARAM+: 7.34 dB, ARAM−: 11.9 dB; p<0.001) and lower RNFL thickness in the inferior peripapillary quadrants compared to ARAM− (RNFL superior: ARAM+ 74.2 μm, ARAM− 77.5 μm; RNFL temporal: ARAM+ 46.8 μm, ARAM− 53.0 μm, p<0.001; and RNFL inferior: ARAM+ 63.2 μm, ARAM− 73.1 μm, p<0.001). Within the same eye, ARAM+ showed a lower retinal sensitivity compared to ARAM− ([ARAM− (11.13 dB)] − [ARAM+ (9.56 dB) = 1.57 dB; p=0.25). The proportion of ARAM+ per eye correlated strongly with reduced retinal light sensitivity (p=0.02), corresponding lower peripapillary RNFL thickness (p=0.02), and lower RNFL temporal quadrant thickness (p<0.01), but not with greater age (p=0.45). Conclusion. ARAM was more frequently identified in the eyes with a lower retinal sensitivity and peripapillary RNFL thickness and may be a clinical sign in the macula for an advanced stage of POAG.